Development of Visual Interface and Hardware Logic for Open Architecture NC Controller for 3-Axis Simultaneous Interpolation - Kumar, Rahul (My University, 2012)
The trends in the NC machine tool development are towards open architecture control and Direct Model to Part machining strategies. The NC machine requirement of better simplicity,portability, interoperability, adaptability and low cost necessitates the improvement and simplification of conventional NC machining procedures. One major issue with the conventional NC technology is that the motion control in NC machining operations cannot be efficiently automated with the restrictive (ISO 6983) G and M codes. G and M code were designed in the era when paper tapes were used for program input in NC. Nowadays the Gcode programs are generated by the computer aided manufacturing (CAM) tools, using the geometrical data from computer aided design (CAD) tools as input. However, CNCs of different vendors implement different versions of G-code which lacks portability and leads to proprietary CAD–CAM–CNC integrated modules/software. An open architecture control machine tools can be directly controlled from a computer, rather than a dedicated NC controller. This is possible by virtue of high processing speed and low cost of a modern computer. An open architecture NC tool paths is free from conventional ISO G and M based NC tool paths, rather use a file containing the pre-calculated locations of the relative position of the cutter with respect to the work piece in a logical sequence. In the present work a PC based interactive interface and CNC drive control system capable of three axis simultaneous interpolations for sculptured surface machining has been developed. The GUI and NC interface hardware has been developed for a PC controlled 3-axis vertical milling machine which finds its tremendous applications in machining of sculptured surfaces. Some dedicated CNC machines are available for machining sculptured surfaces but because of heavy cost these are not affordable for small scale production work. The development of GUI and the NC hardware along with the logics followed has been explained in the chapter 3 and 4 of this thesis report. The testing and validation of the GUI interface and NC interface hardware has been done using a specially developed electronic hardware using stepper motors. This work is aimed at providing a low cost NC machine interface from PC (GUI) and hardware interface for machine drive control so that the dependency of commercially available NC controllers can be avoided. This is a step towards customised CAD/CAM integration to enable NC machine tool with new control strategies, sensors and interfaces. Also the open architecture based NC system will be better affordable than the commercial NC system for sculptured surface machining.
M.E. (CAD/CAM and Robotics)
Keywords: 3-Axis Vertical Milling; NC Controller